A descriptive analysis of anglicisms used in Ecuadorian newspapers - Alvarez Torres, Efren. Rojas Merchan,Rogelio (2010)
The topic of this study is “A DESCRIPTIVE ANALYSIS OF ANGLICISMS USED IN ECUADORIAN NEWSPAPERS”. The reason for this research is to demonstrate how anglicisms have affected our newspapers which are written in Spanish, and also our way of living. This thesis details the different types of studies done. The research was done in the city of Azogues, in the province of Cañar.